A simplified method of determining the internal structure of amylopectin from barley starch without amylopectin isolation. (1st March 2021) - Zhao, Xue; Andersson, Mariette; Andersson, Roger
Highlights: Determination of the internal structure of whole starch without amylopectin isolation. A simplified method to characterize starch structure of many samples within few days. Building block composition can be obtained to predict functional properties of starch. Abstract: To determine the internal structure of barley starch without amylopectin isolation, whole starch was hydrolyzed using β-amylase to remove the linear amylose and obtain β-limit dextrins (β-LDs). The β-LDs were treated with extensive α-amylase to prepare α-limit dextrins (α-LDs), and the α-LDs were further hydrolyzed with β-amylase into building blocks. The chain-length distribution of β-LD and building block composition were analyzed by size-exclusion chromatography and anion-exchange chromatography. The internal structure of the barley whole starches had similar pattern to barley amylopectins analyzed by conventional methods. The starch of barley amo1 -mutated varieties contained more short internal B-chains and less long internal B-chains than that of other varieties. The starch from amo1 -mutated varieties had more large building blocks than that from waxy varieties. The simplified method presented in this study can effectively characterize starch internal structure that relates to physicochemical properties of starch, although some details of amylopectin structure are not assessable.